The effectiveness of da'wah programmes by Department of Aborigines Affairs (JHEOA) among Native Society: A Case Study in Kg. Tanah Runtoh, Kluang, Johor Darul Ta'zim - Mohd Farhan Bin Abu Amin (Universiti Sains Islam Malaysia, 2022)
The approaches of da'wah it's one of the methods in da'wah propagation towards Muslims and Non-Muslim. However, the effectiveness of performance and propagation is important in the message of da'wah own. Thus, the study will try to explore using the effectiveness of da'wah methodology towards Non-Muslim especially to society of Orang Asli, which reception of the Islamic religion as practical to profess. Therefore, the writer tries to obtain the effective types of da'wah towards Native Society (Orang Asli) with measurement of their reactions. Then, the writer makes calculating the effectiveness of methods da'wah from past researchers and literature review to progress in other situation. The study in Perkampungan Orang Asli Tanah Runtoh, Kluang, Johor showing that is prove towards one of the da'wah programs. It's most important to newly of da'i to propagate the messages of da'wah towards them in future times.